Demography and Dispersal Ability of a Threatened Saproxylic Beetle: A Mark- Recapture Study of the Rosalia Longicorn (Rosalia alpina) - Drag, Lukáš (Jihočeská univerzita, 2016)
This thesis focuses on demography and mobility of an endangered and strictly protected icon of European saproxylic biodiversity, the Rosalia longicorn beetle (Rosalia alpina). Using the mark-recapture method we estimated the size of the population, adult longevity, and dispersal ability of the Rosalia longicorn on three hills in the Ralska Upland, Czech Republic. Furthermore, we assessed the distribution pattern of another 15 populations inhabiting small patches of old beech forest in this area. Factors affecting local survival and the species conservation are discussed.
Demography and Dispersal Ability of a Threatened Saproxylic Beetle: A Mark-Recapture Study of the Rosalia Longicorn (Rosalia alpina)
Keywords: insect ecology; Natura 2000; Fagus sylvatica; metapopulation; insect ecology; Natura 2000; Fagus sylvatica; metapopulation